Kemerosotan Moral Di Kalangan Remaja: Sebuah penelitian Mengenai Parenting Styles dan Pengajaran Adab - Diah Ningrum (Universitas Islam Indonesia, 2015)
Many reserach and surveys have been conducted to find out the types and levels of moraldecadence among Indonesian youth. The objective of the current study is to show thisphenomenon and to investigate whether parenting styles are related to the increased ordecreased of incidences of moral decadence. The next focus is to relate the concept of Adab (anIslamic ethics) as defined by Al Ghazali to effective parenting styles that may reduce moraldecadence among youth. The method used is qualitative method based on focus groupdiscussion among parents in order to find out parenting styles applied in their families. Inaddition, document analysis is also used such as published official data, and reserach reports.The findings showed that there is relationship between parenting styles and moral decadenceamong youth. The researcher suggested that effective parenting styles should be related toteaching of Adab.